Written and Non-Written Communication Methods as Correlates of Employee Performance: A Study of Academic Staff of Primary Teachers’ Colleges in Central Uganda - Kasande Byakutaga, Beatrice N.; Onen, David; Oonyu, Joseph; Kasesene, Edris S. (Journal of Education and Practice, 2016)
This study delved into how written and non-written communication methods are correlated with the performance of the academic staff of Primary Teachers’ Colleges (PTCs) in Central Uganda. The study was prompted by reportedly the deteriorating performance of the academic staff of most PTCs in the country despite government’s efforts to train and motivate them. The study employed a correlational cross-sectional survey design where both quantitative and qualitative data were collected from a total of 120 respondents comprised of 5 Principals, 7 Deputy Principals, 13 Heads of Department and 95 members of the Academic Staff using questionnaire survey and interview methods. The data were analyzed with the use of descriptive and inferential statistical techniques as well as content analysis method. Study results revealed that non-written communication methods generally have a statistically weak correlation (r=.380, p=.146) with the performance of the academic staff while written communication methods – whether personally or impersonally addressed - revealed a statistically significant correlation (r=.912, p=.000) with the performance of the academic staff. The researchers thus concluded that the kind of communication methods that managers/administrators employ on their staff have a bearing on how their staff perform their jobs. Thus, it was recommended that colleges’ administrators as well as those concerned with communicating with the academic staff of PTCs should carefully select from the array of available communication methods those that have significant positive correlations with the performance of the staff in order to enhance their job performance as well as that of the entire institution.
Keywords: Communication methods; Academic staff; Performance; Primary teachers’ colleges